PERENCANAAN KEUANGAN MADRASAH DAN PRAKTIK TRANSPARANSI ANGGARAN DI MA AL-HOLILIYAH CIDAUN: STUDI KUALITATIF DESKRIPTIF - Sumiati, Epi Fitria (Epistemic: Jurnal Ilmiah Pendidikan, 2026)
This study examines the practices of financial planning and budget transparency at MA Al-Holiliyah Cidaun Cianjur using a descriptive qualitative approach. Given that previous research on madrasah financial governance is still limited to conventional approaches, this study explores the integrative application of strategic environmental analysis (PESTLE and SWOT) in madrasah financial planning. Data were obtained through document analysis of the Madrasah Work Plan and financial reports, as well as non-participant observation of administrative practices. The data were then analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate that annual budgeting is conducted through internal coordination. However, the transparency of financial information remains limited to internal stakeholders and has not been consistently communicated to external parties. The novelty of this study lies in the development of an integrative PESTLE-SWOT model contextualized to analyze the dynamics of madrasah finances. Planning documents have proven to be not merely administrative requirements but vital instruments of accountability. The results of this study provide practical contributions for madrasah administrators in formulating adaptive planning, as well as theoretical contributions in enriching the literature on strategic management in Islamic education.